The Information Society: An Introduction - Ziya Kutluoğlu (Türk Kütüphaneciliği)
Many researchers/authors try to explain what information society is, how it appeared in the first place and what the components of such a society are. In this contest, Armand Mattelart also tries to answer these questions in his work named The Information Society: An Introduction. The author indicates that the main purpose of this book is to define the concepts, discussions and reviews related to the information society.